2017
DOI: 10.1002/anie.201610619
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of CH3NH3PbBr3 Nanoplatelets with Polarized Emission through Self‐Organization

Abstract: We report a combined experimental and theoretical study of the synthesis of CH NH PbBr nanoplatelets through self-organization. Shape transformation from spherical nanodots to square or rectangular nanoplatelets can be achieved by keeping the preformed colloidal nanocrystals at a high concentration (3.5 mg mL ) for 3 days, or combining the synthesis of nanodots with self-organization. The average thickness of the resulting CH NH PbBr nanoplatelets is similar to the size of the original nanoparticles, and we al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 45 publications
3
76
0
2
Order By: Relevance
“…(d) The procedure for preparing CH 3 NH 3 PbI 3 plates on a patterned substrate [52]. (e) Self-transformation of CH 3 NH 3 PbBr 3 nanodots to nanoplatelets [53]. The enlarged parts represent the corresponding TEM images of CH 3 NH 3 PbBr 3 nanocrystals.…”
Section: Other Synthesis Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(d) The procedure for preparing CH 3 NH 3 PbI 3 plates on a patterned substrate [52]. (e) Self-transformation of CH 3 NH 3 PbBr 3 nanodots to nanoplatelets [53]. The enlarged parts represent the corresponding TEM images of CH 3 NH 3 PbBr 3 nanocrystals.…”
Section: Other Synthesis Methodsmentioning
confidence: 99%
“…Liu et al demonstrated the self-organization process for the transformation of CH 3 NH 3 PbBr 3 nanodots (NDs) to NPLs [53]. In detail, the CH 3 NH 3 PbBr 3 NDs were dissolved in a nonpolar solvent and aged in darkness (Figure 3e).…”
Section: Two-dimensional Materials For Photodetectormentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Liu et al. synthesized uniform and luminescent CH 3 NH 3 PbBr 3 nanoplatelets through self‐organization of preformed colloidal CH 3 NH 3 PbBr 3 nanodots based on dipole–dipole interactions …”
Section: Structural Control Of Lead Halide Perovskite Nanocrystalsmentioning
confidence: 99%